2009
DOI: 10.1007/s10072-009-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bilateral cortical representation patterns in writer’s cramp: a functional magnetic resonance imaging study at 3.0 T

Abstract: Functional magnetic resonance imaging was used to characterize patterns of cortical activation in response to sensory and motor tasks in patients with writer's cramp. 17 patients and 17 healthy subjects were examined during finger-tapping, index finger flexion, and electrical median nerve stimulation of both hands during electromyographic monitoring. SPM2 was used to evaluate Brodmann area (BA) 4, 1, 2, 3, 6, 40. Patients showed decreased activation in the left BA 4 with motor tasks of both hands and the left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Similar to positron emission tomography and structural imaging studies, this line of research again confirmed the presence of alterations in basal ganglia, thalamus, cerebellum and sensorimotor cortex across different forms of isolated dystonia and hinted to abnormal integration of sensorimotor information flow within the basal ganglia-thalamo-cortical and cerebello-thalamo-cortical circuitries (e.g. Baker, Andersen, Morecraft, & Smith, 2003; Burciu et al, 2017; Butterworth et al, 2003; Haslinger, Altenmuller, Castrop, Zimmer, & Dresel, 2010; Hu, Wang, Liu, & Zhang, 2006; Islam et al, 2009; Kadota et al, 2010; Pujol et al, 2000; Simonyan & Ludlow, 2010). Additionally, some studies pointed to abnormal sensory processing by primary somatosensory cortex that may contribute to the pathophysiology of dystonia (Dresel, Haslinger, Castrop, Wohlschlaeger, & Ceballos-Baumann, 2006; Haslinger et al, 2010; Simonyan & Ludlow, 2010), whereas others mapped abnormal somatotopy of digit representation in primary somatosensory cortex and putamen in focal hand dystonia (Butterworth et al, 2003; Delmaire et al, 2005; Nelson, Blake, & Chen, 2009).…”
Section: Functional Neuroimaging Of Dystoniasupporting
confidence: 64%
“…Similar to positron emission tomography and structural imaging studies, this line of research again confirmed the presence of alterations in basal ganglia, thalamus, cerebellum and sensorimotor cortex across different forms of isolated dystonia and hinted to abnormal integration of sensorimotor information flow within the basal ganglia-thalamo-cortical and cerebello-thalamo-cortical circuitries (e.g. Baker, Andersen, Morecraft, & Smith, 2003; Burciu et al, 2017; Butterworth et al, 2003; Haslinger, Altenmuller, Castrop, Zimmer, & Dresel, 2010; Hu, Wang, Liu, & Zhang, 2006; Islam et al, 2009; Kadota et al, 2010; Pujol et al, 2000; Simonyan & Ludlow, 2010). Additionally, some studies pointed to abnormal sensory processing by primary somatosensory cortex that may contribute to the pathophysiology of dystonia (Dresel, Haslinger, Castrop, Wohlschlaeger, & Ceballos-Baumann, 2006; Haslinger et al, 2010; Simonyan & Ludlow, 2010), whereas others mapped abnormal somatotopy of digit representation in primary somatosensory cortex and putamen in focal hand dystonia (Butterworth et al, 2003; Delmaire et al, 2005; Nelson, Blake, & Chen, 2009).…”
Section: Functional Neuroimaging Of Dystoniasupporting
confidence: 64%
“…Therefore, results of different studies are difficult to compare to each other. Fifth and finally, in only one of the fMRI studies the task was monitored with EMG (Islam et al, 2009). This way, it is unknown whether tasks were correctly executed, when tasks were performed and whether dystonic activity occurred.…”
Section: Discussionmentioning
confidence: 99%
“…These changes were observed in a study using motor tasks performed with the dystonic and the clinically asymptomatic hand and compared to healthy controls performing these tasks with both hands. The cortical activation pattern differed between tapping and flexion in the withinsubject comparison: the abnormalities were more widespread while performing the repetitive movement tapping even though there were no dystonic muscle contractions (Islam et al, 2009). …”
Section: Functional Mrimentioning
confidence: 96%
“…Indeed if FHD patients are asked to physically perform movements, neural activity has been reported to be abnormal in a very heterogeneous network, including basal ganglia (Chase et al, 1988; Siebner et al, 2003; Blood et al, 2004; Peller et al, 2006; Schneider et al, 2010), thalamus (Preibisch et al, 2001; Hu et al, 2006), sensory-motor cortex (Preibisch et al, 2001; Islam et al, 2009; Jankowski et al, 2013), supplementary motor area (Oga et al, 2002; Hu et al, 2006), prefrontal cortex (Playford et al, 1998; Pujol et al, 2000; Preibisch et al, 2001; Dresel et al, 2006), and primary motor cortex (M1; Ceballos-Baumann et al, 1995; Playford et al, 1998; Ibanez et al, 1999; Pujol et al, 2000; Detante et al, 2004; Dresel et al, 2006). However, there is strong evidence supporting the position that the sensory feedback during movement execution is altered in FHD and other forms of focal dystonia (see Defective Learning-based Sensory-Motor Integration).…”
Section: Sensory-motor Deficits In Focal Dystoniamentioning
confidence: 99%